Xyloglucan and Its Biosynthesis - Zabotina, Olga A. (Frontiers in Plant Science, 2012)
The hemicellulosic polysaccharide xyloglucan (XyG), found in the primary cell walls of most plant tissues, is important for structural organization of the cell wall and regulation of growth and development. Significant recent progress in structural characterization of XyGs from different plant species has shed light on the diversification of XyG during plant evolution. Also, identification of XyG biosynthetic enzymes and examination of their interactions suggests the involvement of a multiprotein complex in XyG biosynthesis. This mini-review presents an updated overview of the diversity of XyG structures in plant taxa and recent findings on XyG biosynthesis.